Efficacy and Feasibility of an Osteopathic Intervention for Neurocognitive and Behavioral Symptoms Usually Associated With Fetal Alcohol Spectrum Disorder - Cases-Solé, Ramon; Varillas-Delgado, David; Astals-Vizcaino, Marta; García-Algar, Óscar (Frontiers in Behavioral Neuroscience, 2022)
The purpose was to evaluate the efficacy of a four-week planned osteopathic manipulative treatment intervention on the improvement of neurocognitive and behavioral symptoms usually associated with fetal alcohol spectrum disorder. Children aged 3-6 years with low level of attention from two schools and an osteopathic center were recruited in a prospective randomized pilot study in an osteopathic manipulative treatment group (osteopathic manipulative treatment and standard support measures) or a control group (standard support measures). Neuropsychological maturity test results for attention, iconic memory, spatial structuration, and visual perception were recorded at baseline and post-intervention. Thirty-two symptomatic participants without fetal alcohol spectrum disorder were included in the analyses, 16 in each group. Male: female ratio was 17:15, 10:6 in the osteopathic manipulative treatment group and 7:9 in the control group. No adverse effects were communicated and there were no dropouts. Intergroup post-intervention statistical differences for attention, spatial structuration, and iconic memory were p=0.011, p<0.001, and p<0.001, respectively; no differences were seen for visual perception (p=0.236). This study shows that a four-week osteopathic manipulative treatment intervention may be a feasible and effective therapeutic approach for neurocognitive and behavioral symptoms usually present in fetal alcohol spectrum disorder, justifying more studies on children affected by this condition.